Kritik orientalis terhadap tasawuf: antara distorsi dan pemahaman - Shoopa Alifiah Salsabil; Suadi Sa'ad (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2026)
This study aims to analyze Orientalist critiques of Sufism and to understand how Muslim scholars and practitioners respond to the epistemological constructions developed by Western thought toward Sufi teachings. This phenomenon is significant because Orientalist criticism often distorts the essence of Islamic spirituality by portraying Sufism as a product of non-Islamic cultural assimilation. The study employs a descriptive qualitative approach using the library research method, examining various primary and secondary sources such as the works of Orientalists (Reynold A. Nicholson, Louis Massignon, and Edward Said) and contemporary Muslim scholars (Syed Naquib Al-Attas, Amin Abdullah, and Rahmawati). Data were collected through documentation and analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and verification to identify key themes. The findings reveal that Orientalist critiques of Sufism are grounded in a rationalistic-secular paradigm that neglects the spiritual and revelatory dimensions of Islam. Conversely, Muslim scholars affirm that Sufism is rooted in the Qur’an and the Sunnah, emphasizing the principles of tazkiyatun nafs (purification of the soul), ihsan (spiritual excellence), and tawhid (oneness of God). Three main themes emerge: (1) the epistemological distortion by Orientalists regarding the sources of Sufi teachings, (2) the reconstructive responses of Muslim scholars through the Islamization of knowledge, and (3) the de-Orientalization of Islamic studies as a form of epistemic justice. Theoretically, this research enriches the discourse on Islamic epistemology and postcolonial studies, while practically it offers new directions for developing Islamic curricula that integrate rationality and spirituality. Future studies are suggested to use a phenomenological field approach to examine the empirical experiences of Sufi communities in confronting Western knowledge hegemony.